2012
DOI: 10.1038/onc.2012.397
|View full text |Cite
|
Sign up to set email alerts
|

Immunobiology of human mucin 1 in a preclinical ovarian tumor model

Abstract: Epithelial ovarian cancer is an aggressive malignancy, with a low 5-year median survival. Continued improvement on the development of more effective therapies depends in part on the availability of adequate preclinical models for in vivo testing of treatment efficacy. Mucin 1 (MUC1) glycoprotein is a tumor-associated antigen overexpressed in ovarian cancer cells, making it a potential target for immune therapy. To create a preclinical mouse model for MUC1-positive ovarian tumors, we generated triple transgenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(61 citation statements)
references
References 55 publications
2
59
0
Order By: Relevance
“…The mouse tumors show similarly increased epithelial cell expression of complement proteins (Fig. 4A), further demonstrating that the MUC1KrasPten mouse model, which replicates with high fidelity the histopathology of human EAOC (21, 28), may also provide an useful preclinical tool for exploring the complement biology in the ovarian tumor microenvironment.…”
Section: Resultsmentioning
confidence: 64%
See 3 more Smart Citations
“…The mouse tumors show similarly increased epithelial cell expression of complement proteins (Fig. 4A), further demonstrating that the MUC1KrasPten mouse model, which replicates with high fidelity the histopathology of human EAOC (21, 28), may also provide an useful preclinical tool for exploring the complement biology in the ovarian tumor microenvironment.…”
Section: Resultsmentioning
confidence: 64%
“…To accomplish this, we employed ovarian surface epithelial cells derived from triple transgenic mice that progress to human mucin 1 (MUC1) - expressing endometrioid ovarian cancer that closely mirrors the human disease (21). The mice heterozygously express human MUC1 as a transgene, and simultaneously carry the conditional LoxP-Stop-LoxP K-ras G12D oncoallele and the floxed Pten loxP/loxP gene (28).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To further explore this mechanism, we employed triple transgenic mice that progress to EAOC closely mirroring the human disease. 6,7 Using this preclinical model, we demonstrated that complement upregulation in epithelial cells occurs early in carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%